Entomological Assessment of Mosquito Diversity and Density in Negara District, Bali: Implications for Vector-Borne Disease Surveillance - Widyawati, Dani Sari; Duhita, Maharani Retna (HAYATI Journal of Biosciences, 2026)
Indonesia has one of the highest prevalences of malaria in Asia, with annual case numbers on the rise. Despite being a major international tourist destination, the Negara Sub-district in Jembrana Regency, Bali, continues to experience notable incidences of both diseases. Entomological surveys are crucial for evaluating mosquito diversity and density, which supports effective vector control strategies. This study, conducted in five villages from September to October 2024, employed entomological survey methods to calculate the House Index (HI), Container Index (CI), Breteau Index (BI), and Density Figure (DF). Mosquito species diversity was assessed using the Shannon-Wiener diversity index and evenness (E) and dominance (C) metrics. Results indicated that HI, CI, and BI values were within the low transmission risk category, with a DF of 4 and a larva-free rate (ABJ) of ≤95%. Six mosquito species were identified: Aedes aegypti, Aedes albopictus, Anopheles dirus, Armigeres subalbatus, Culex quinquefasciatus, and Mansonia uniformis. The species diversity was moderate (1 < H' ≤ 3), even species distribution (E > 0.6), and low dominance (C ≤ 0.5). These findings suggest a relatively low risk of vector-borne disease transmission. However, given the presence of multiple disease-vector species and the region's dynamic human activity, continuous entomological surveillance remains essential to anticipate population surges and strengthen disease prevention efforts.